2020
DOI: 10.3390/nano10102063
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Graphene/Silver Nanowire Hybrid Fillers on Highly Stretchable Strain Sensors Based on Spandex Composites

Abstract: Embedding conductive nanomaterials into elastomeric polymer matrices is one of the most promising approaches for fabricating stretchable strain sensors capable of monitoring large mechanical movements or deformation through the detection of resistance changes. Here, hybrid fillers comprising graphene and silver nanowires (AgNWs) are incorporated into extremely stretchable spandex to fabricate strain sensors. Composites containing only graphene and those containing the graphene/AgNW hybrid fillers are systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 55 publications
(79 reference statements)
0
10
0
Order By: Relevance
“…It is because electrical charges only transfer from AgNWs to AgNWs before composition and GR can bridge AgNWs, which can provide more conductive paths after composition. 36 In addition, comparing with the sheet resistance of AgNW films, the sheet resistance AgNWs/GR films changes a little. As Figure 2b shows, the conductivity of the film was further improved by the encapsulant of PEDOT:PSS.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…It is because electrical charges only transfer from AgNWs to AgNWs before composition and GR can bridge AgNWs, which can provide more conductive paths after composition. 36 In addition, comparing with the sheet resistance of AgNW films, the sheet resistance AgNWs/GR films changes a little. As Figure 2b shows, the conductivity of the film was further improved by the encapsulant of PEDOT:PSS.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…As Figure b shows, the conductivity of the film was further improved by the encapsulant of PEDOT:PSS. It was because the addition of PEDOT:PSS provided more conductive paths and charges can transfer from AgNWs to GR and to PEDOT:PSS. , In addition, the variance of AgNWs/GR/PEDOT:PSS film sheet resistance was more stable than that of AgNWs/GR film sheet resistance. Figure c shows the transmittances of the AgNW film, AgNWs/GR film, and AgNWs/GR/PEDT:PSS film.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensor was able to withstand more than a million stretch–release cycles in addition to a stretchability of 58% and a gauge factor of 1591. In another instance, reduced graphene flakes and AgNWs were used as fillers on a spandex fibrous substrate by Tan Thong Vo et al to realize a stretchable strain sensor [ 111 ]. It was identified that the increase in a single filler alone results in reduced stretchability.…”
Section: Agnw/other Substrate-based Stretchable Strain Sensorsmentioning
confidence: 99%
“…The oxidation of graphite, subsequent exfoliation of graphite oxide to GO, and eventual chemical or thermal reduction of GO is a scalable and inexpensive technique to obtain substantial quantities of graphene flakes [ 16 ]. GO and reduced graphene oxide (rGO) have been extensively utilized as components of paper-like materials [ 17 , 18 ], nanocomposites [ 15 , 19 ], electrodes for energy storage devices [ 20 , 21 ], transparent conducting films [ 22 ], and high-performance coatings [ 23 ]. However, the oxidation of graphite induces the formation of numerous defects and oxygen functional groups [ 24 ].…”
Section: Introductionmentioning
confidence: 99%